Exploring the impact of organizational characteristics on research agendas across scientific fields - Santos, J. M. (2024)
An increasing culture of performativity has led to changes in the organizational landscape of academic institutions. While the impact of these changes on outputs is well documented, their impact on academics’ strategic research agendas is still an emerging topic. This study expands upon previous research on this issue and focuses on comparing these dynamics across all fields of science using a global sample of academics. We found that most of the relationships between organizational features and research agendas were mostly consistent across disciplines, with variations mainly in the strength rather than the direction of effects. The perceived access to resources, autonomy, and collegiality was the key driver in promoting ambitious, collaborative, discovery-driven, and multidisciplinary agendas. Furthermore, our findings suggest a concerning trend in research institutions: academics that are more willing to stay in their institutions and are more aligned with its demands are less inclined to pursue trailblazing agendas. Although most of these effects were universal, some field-specific dynamics are also discussed, notably in what concerns the so-called “hard” sciences. This study highlights the importance of promoting a collegial environment with a high degree of autonomy to foster discovery-driven research and underscores the potential risks of the “publish or perish” culture prevalent in academia.